A scalable 12-week exercise and education programme reduces symptoms and improves function and wellbeing in people with hip and knee osteoarthritis - Smith, Jemma L.; Innes, Aidan Q.; Burns, Danielle S.; Deniszczyc, Davina; Selfe, James; MacConville, Stephen; Deighton, Kevin; Kelly, Benjamin M. (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Osteoarthritis is a chronic musculoskeletal condition that impacts more than 300 million people worldwide, with 43 million people experiencing moderate to severe disability due to the disease. This service evaluation provides the results from a tailored blended model of care on joint health, physical function, and personal wellbeing. Methods: 1593 adult participants with osteoarthritis completed the Nuffield Health Joint Pain Programme between February 2019 and May 2022. The 12-week programme included two 40-minute exercise sessions per week. All exercise sessions were conducted face-to-face and were followed by 20 minutes of education to provide information and advice on managing osteoarthritis. Results: The 12-week joint pain programme significantly improved Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) global scores (Week 0: 37.5 [17.2]; Week 12: 24.0 [16.6]; p < 0.001), as well as subscales for pain (Week 0: 7.6 [3.7]; Week 12: 4.9 [3.7]; p < 0.001), function (Week 0: 26.0 [13.0]; Week 12: 16.3 [12.4]; p < 0.001), and stiffness (Week 0: 3.9 [1.6]; Week 12: 2.8 [1.7]; p < 0.001). Significant improvements in health-related outcomes including systolic and diastolic blood pressure (Week 0: 139 [18] mmHg; Week 12: 134 [17] mmHg, and Week 0: 82 [11] mmHg; Week 12: 79 [19] mmHg; both p < 0.001), body mass index (Week 0: 29.0 [4.5] kg/m2; Week 12: 28.6 [4.4] kg/m2; p < 0.001), waist to hip ratio (Week 0: 0.92 [0.23]; Week 12: 0.90 [0.11], p < 0.01) and timed up and go (Week 0: 10.8 seconds [2.9]; Week 12: 8.1 seconds [2.0]; p < 0.001) were also observed. On completion of the joint paint programme, participants also reported significant improvements in all assessed aspects of self-reported wellbeing (all p < 0.001). Discussion: With reductions in physical symptoms of osteoarthritis and improvements in personal wellbeing, the joint pain programme delivered by personal trainers in a gym-setting offers a nationally scalable, non-pharmacological treatment pathway for osteoarthritis.